2011
DOI: 10.1080/13607863.2011.596805
|View full text |Cite
|
Sign up to set email alerts
|

Underdiagnosis of dementia in primary care: Variations in the observed prevalence and comparisons to the expected prevalence

Abstract: Just under a half of the expected numbers of patients with dementia are recognised in GP dementia registers. The underdiagnosis of dementia varies with practice characteristics, socio-economic deprivation and between PCTs, which has implications for the local implementation of the National Dementia Strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
188
3
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(208 citation statements)
references
References 26 publications
6
188
3
5
Order By: Relevance
“…GPs from larger practices were more likely to correctly rule-out dementia. Interestingly, Connolly et al (2011) reported lower rates of diagnosis in practices with one GP as opposed to several. They considered that one of the reasons for this may have been lack of time for the solo GP.…”
Section: Discussionmentioning
confidence: 95%
“…GPs from larger practices were more likely to correctly rule-out dementia. Interestingly, Connolly et al (2011) reported lower rates of diagnosis in practices with one GP as opposed to several. They considered that one of the reasons for this may have been lack of time for the solo GP.…”
Section: Discussionmentioning
confidence: 95%
“…Alzheimer's disease does not have a diagnostic test for confirmation purposes (St Germaine-Smith et al, 2012) and underdiagnosis of dementia is a significant problem (Boustani et al, 2003;ADI, 2011;Connolly et al, 2011). Therefore, the case definition for the present study prioritized sensitivity over specificity by including prescription drug and long-term care data to account for dementia cases that may not have been identified in physician or hospital data.…”
Section: Cohortmentioning
confidence: 99%
“…All patients on dementia registers were included; however, dementia may remain undiagnosed in up to 50% of patients, which could have led to underestimation of true effect. 41 Measures of care that rely on the evaluation of medical records, such as history taking, have been associated with poorer overall quality of care 42 and medical records may not give an accurate reflection of the actual care provided. However, documented care is, in itself, a measure of quality.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…• the detection rates of dementia, and associated behavioural and psychological symptoms of dementia; [22][23][24] • end-of-life care; 25 and…”
Section: Introductionmentioning
confidence: 99%